A tool to guide species and seed selection for the restoration of seasonally dry tropical forest in Colombia - Thomas, E. (Bioversity International and the International Center for Tropical Agriculture, 2016)
Making sure that native species and seed sources are site-adapted requires a certain degree of scientifically-based decision making capacity, which most restoration practitioners currently do not have. As part of our CBD COP13 Forest and Landscape Restoration blog series, Evert Thomas writes about how Bioversity International scientists are working to overcome this.